Current smoking and COVID-19 risk: results from a population symptom app in over 2.4 million people. Issue 7 (5th January 2021) - Hopkinson, Nicholas S; Rossi, Niccolo; El-Sayed_Moustafa, Julia; Laverty, Anthony A; Quint, Jennifer K; Freidin, Maxim; Visconti, Alessia; Murray, Ben; Modat, Marc; Ourselin, Sebastien; Small, Kerrin; Davies, Richard; et al.
Abstract : Background: The association between current tobacco smoking, the risk of developing symptomatic COVID-19 and the severity of illness is an important information gap. Methods: UK users of the Zoe COVID-19 Symptom Study app provided baseline data including demographics, anthropometrics, smoking status and medical conditions, and were asked to log their condition daily. Participants who reported that they did not feel physically normal were then asked by the app to complete a series of questions, including 14 potential COVID-19 symptoms and about hospital attendance. The main study outcome was the development of 'classic' symptoms of COVID-19 during the pandemic defined as fever, new persistent cough and breathlessness and their association with current smoking. The number of concurrent COVID-19 symptoms was used as a proxy for severity and the pattern of association between symptoms was also compared between smokers and non-smokers. Results: Between 24 March 2020 and 23 April 2020, data were available on 2 401 982 participants, mean (SD) age 43.6 (15.1) years, 63.3% female, overall smoking prevalence 11.0%. 834 437 (35%) participants reported being unwell and entered one or more symptoms. Current smokers were more likely to report symptoms suggesting a diagnosis of COVID-19; classic symptoms adjusted OR (95% CI) 1.14 (1.10 to 1.18); >5 symptoms 1.29 (1.26 to 1.31); >10 symptoms 1.50 (1.42 to 1.58). The pattern of association between reported symptoms did not vary between smokers and non-smokers. Interpretation: These data are consistent with people who smoke being at an increased risk of developing symptomatic COVID-19.